Associations between fear of COVID-19, dental anxiety, and psychological distress among Iranian adolescents - Maryam Tofangchiha; Chung-Ying Lin; Janneke F. M. Scheerman; Anders Broström; Hanna Ahonen; Mark D. Griffiths; Santosh Kumar Tadakamadla; Amir H. Pakpour (BDJ Open, 2022)
Abstract Objectives The present study evaluated the association of fear of COVID-19 with dental anxiety, oral health-related quality of life (OHRQoL), and psychological distress (depression, anxiety and stress), as well as exploring the mediating role of dental anxiety in the association of fear of COVID-19 with OHRQoL and psychological distress. Methods A cross-sectional study was conducted among adolescents in high schools of Qazvin city (Iran) from March-June 2021, recruited through a two-stage cluster sampling method. All the adolescents completed a self-administered survey assessing (i) fear of COVID-19, (ii) depression, anxiety and stress, (iii) OHRQoL, and (iv) dental anxiety. Structural equation modelling was used to evaluate all the hypothesised associations, and the model fit was estimated. Results A total of 2429 adolescents participated in the study. The conceptual model fitted the data well. Fear of COVID-19 had a direct effect on dental anxiety (B = 0.316; bias-corrected bootstrapping 95% CI = 0.282, 0.349), depression (B = 0.302; bias-corrected bootstrapping 95% CI = 0.259, 0.347), anxiety (B = 0.289; bias-corrected bootstrapping 95% CI = 0.246, 0.334), stress (B = 0.282; bias-corrected bootstrapping 95% CI = 0.237, 0.328), and OHRQoL (B = −0.354; bias-corrected bootstrapping 95% CI = −0.530, −0.183). Also, dental anxiety mediated the association of fear of COVID-19 with depression, anxiety stress, and OHRQoL. Conclusions High levels of fear of COVID-19 were associated with high levels of dental anxiety and poorer OHRQoL. Moreover, fear of COVID-19 was positively associated with anxiety, depression and stress. Increased levels of dental anxiety were also associated with increased anxiety, stress, depression, and poorer OHRQoL.